Financial performance evaluation of firms in BIST 100 index with ITARA and COBRA methods - Ali Katrancı; Nilsen Kundakcı; Dragan Pamucar (Financial Innovation)
Abstract Evaluating firms’ financial performance is important for survival in the competitive environment arising from technological advancements and gaining a competitive advantage. This study aims to assess the financial performances of firms traded on the Istanbul Stock Exchange 100 Index (Borsa Istanbul (BIST) 100 Index) between 2018 and 2022 using an integrated multi-criteria decision-making (MCDM) method. This is the first study to use a new combined approach proposed based on the indifference threshold-based attribute ratio analysis (ITARA) and cost estimation, benchmarking, and risk assessment (COBRA) methods, which have not been applied to corporate performance assessment. The ITARA method is used to find the weights of the criteria, and the ranking of the firms in terms of financial performance is obtained using the COBRA method. The results show that the firms with the highest financial performance are ISMEN, ALGYO, PGSUS, KOZAA, and IPEKE. The companies with the lowest financial performance are AKFGY, BAGFS, MGROS, KOZAL, and GOZDE. The results of this ranking provide important information for firms to recognize their position and for investors who want to invest in firms in the BIST 100 Index. Additionally, sensitivity analyses are performed to assess the impact of changes in the criteria on the ranking of the firms and to validate the results of the proposed method. A comparative analysis is made with different MCDM methods like the technique for order preference by similarity to ideal solution (TOPSIS), and combined compromise solution (CoCoSo) methods and Spearman’s rank correlation test results are presented. This approach leads to the conclusion that the proposed approach can be a useful and effective tool for assessing the financial performance of firms.